Pesticide Options for Important Insect, Mite and Mollusk Pests of Commercial Flowers in Florida - James F. Price; Curtis Nagle; Elzie McCord, Jr. (EDIS)
This insect control guide is a summary of chemical control measures that are presently available to commercial flower producers in Florida and includes beneficial nematode and microbial insecticides that also are components of biological control. This document is ENY-695, one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 2003. Revised: September 2004.